Reduction of Left Atrium During Isolated Mitral Valve Replacement - V. Popov; V. Beshlyaga; V. Zaharova; K. Pukas; V. Roy; N. S. Osypenko; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2016)
Objective is to determined possibillities of left atrium (LA)s reduction (LAR) during mitral valve replacement (MVR).During 1.01.2000–1.01.2012 y. 553 adult patients (pts) were operated with MVD and dilatation of LA at Institute. MVR were performed in all pts. LAR including ligation of LA`s auriculum was performed in 353 pts (group A) and in other 182 pts only MVR (group B). All operations were performed with cardiopulmonary bypass and moderate hypothermia with crystalloid cardioplegia. There were 7 deaths at the hospital period (hospital mortality (HM) – 1,9%) (group A). Data of echo for group A: diameter of LA (mm) preoperative – 62,2±1,4, postoperative – 51,1±1,1, remote period – 52,2±1,2, In group B HM – 2,5%. Data of echo for group B was occurred: diameter of LA preoperative – 58,6±2,4, postoperative – 57,6±4,2, remote period – 69,3±2,2. RAL during isolated MVR was allowing to improve LA`s morphometry during postoperative period comparing with group B (p<0,05).